2022
DOI: 10.3390/ijerph19031127
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Incubation Period among Unvaccinated Delta Variant Coronavirus Disease 2019 Patients in Japan

Abstract: Few studies have assessed incubation periods of the severe acute respiratory syndrome coronavirus 2 Delta variant. This study aimed to elucidate the transmission dynamics, especially the incubation period, for the Delta variant compared with non-Delta strains. We studied unvaccinated coronavirus disease 2019 patients with definite single exposure date from August 2020 to September 2021 in Japan. The incubation periods were calculated and compared by Mann–Whitney U test for Delta (with L452R mutation) and non-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
3
24
1
Order By: Relevance
“…113 Another study reported the incubation period of COVID-19 caused by the Beta/Gamma variant was 5.10 days (95% CI, 4.87-5.33 days). 35 A total of 6 studies reported the incubation period of COVID-19 caused by the Delta variant, including 2 from China, 63,152 2 from Japan, 80,112 1 from France, 35 and 1 from Spain, 26 with a pooled incubation period of 4.41 days (95% CI, 3.76-5.05 days) (Figure 2). Five studies reported the incubation period of COVID-19 caused by the Omicron variant-1 each from Norway, 20 Spain, 26 Japan, 112 the Netherlands, 17 and South Korea 59 -with a pooled incubation period of 3.42 days (95% 2).…”
Section: Mean Incubation Periods Of Covid-19 Infected By Different St...mentioning
confidence: 99%
“…113 Another study reported the incubation period of COVID-19 caused by the Beta/Gamma variant was 5.10 days (95% CI, 4.87-5.33 days). 35 A total of 6 studies reported the incubation period of COVID-19 caused by the Delta variant, including 2 from China, 63,152 2 from Japan, 80,112 1 from France, 35 and 1 from Spain, 26 with a pooled incubation period of 4.41 days (95% CI, 3.76-5.05 days) (Figure 2). Five studies reported the incubation period of COVID-19 caused by the Omicron variant-1 each from Norway, 20 Spain, 26 Japan, 112 the Netherlands, 17 and South Korea 59 -with a pooled incubation period of 3.42 days (95% 2).…”
Section: Mean Incubation Periods Of Covid-19 Infected By Different St...mentioning
confidence: 99%
“…It was shown that the incubation period of SARS-CoV-2 differs from variant to another (Table 1 ). The incubation period for the Delta variant, to the best of our knowledge, was only reported in four studies from China and Japan [ 74 77 ]. It was significantly shorter (3.7, 4.0 and 4.4 days) than for non-Delta strains (4.9–6.0 days) [ 74 76 ].…”
Section: Incubation Periodmentioning
confidence: 99%
“…The incubation period for the Delta variant, to the best of our knowledge, was only reported in four studies from China and Japan [ 74 77 ]. It was significantly shorter (3.7, 4.0 and 4.4 days) than for non-Delta strains (4.9–6.0 days) [ 74 76 ]. However, in another study, a longer incubation period was reported (6.0 days) [ 77 ].…”
Section: Incubation Periodmentioning
confidence: 99%
“…The omicron variant was significantly shorter than that of alpha, delta SI had an intermediate value. These results are surprising as the delta variant R 0 is 1.8 times that of the alpha variant and the omicron variant infectivity is 2.8 times that of delta variant, even if SI among unvaccinated delta variant was not found to be significant from that of unvaccinated non delta variant in one study [2,7,94]. These discrepancies can likely be explained by unvaccinated or "remaining to vaccinate" population either more exposed or more susceptible to new variants, a weaker vaccine effectiveness for delta and omicron variants, and epidemiological surveillance and contact tracing more efficient in their organisation and availability of screening tests throughout the epidemic.…”
Section: Discussionmentioning
confidence: 99%